Synthesis of Poly(hydroxamic Acid)-Poly(amidoxime) Chelating Ligands for Removal of Metals from Industrial Wastewater - M. R. Lutfor; M. Y. Mashitah (E-Journal of Chemistry)
Synthesis of poly(hydroxamic acid)-poly(amidoxime) chelating ligands were carried out from poly(methyl acrylate-co-acrylonitrile) grafted sago starch and hydroxylamine in alkaline medium. The binding property of metal ions was performed and maximum sorption capacity of the copper was 3.20 mmol/ g and the rate of exchange of some metals was faster, i.e. t½ ≈ 7 min (average). Two types of wastewater containing chromium, zinc, nickel, copper and iron, etc. were used and the heavy metal recovery was found to be highly efficient, about 99% of the metals could be removed from the metal plating wastewater.